Optimization of Lasers Parameters for Marking Cylindrical Shanks from SC and Cermet - Zetek, Miroslav; Mrázek, Martin; Zetková, Ivana (Manufacturing Technology Journal, 2016)
Industrial laser marking of the parts is used for the long life identification. For these the micro engraving and annealing are used. The main requirements for the marking are visibility, readability, stability and especially surface without surface modification or defects. In case of the cutting tools main marking are made on the cutting tool shank so it is necessary to use the correct parameters of the marking setup. The marking must be made without change of accuracy and surface quality. When the bad parameters are used the sharp edges are created on the edge of the descriptions. These edges cause gradually damage of the clamping surface and it causes gradually loss of clamping accuracy. So it is a very important to use optimal parameters which depend on the marking material. These article deal with process optimization of the laser marking parameters when the sintered carbide and cermet are used. The laser parameters like laser power, scanning speed and frequency were change and surface quality was evaluated by the optical microscope IFM G4.
Keywords: Laser marking; sintered carbide; cermet; surface quality